Biochemical characterization of a low-affinity arginine permease from the parasite Trypanosoma cruzi - Canepa, Gaspar Exequiel (2004)
Trypanosoma cruzi, the etiological agent of Chagas disease, uses arginine for several metabolic processes, including energy reserves management. In the present work, a novel low-affinity arginine transport system has been studied. Maximum velocity (97 pmol min−1 per 107 cells), and an estimate for the apparent Km value (350 ìM) of this arginine transporter, were 6-fold and 80-fold higher respectively, when compared with the previously described high-affinity arginine transport system. This transport activity seems to be H+-mediated, presents a broad specificity by other amino acids such as methionine, and is regulated along the parasite growth curve and life cycle.